Knowledge and practice of the use of personal protective equipment in the context of Covid 19 in the health personnel of the ICU service of the Hospital El Carmen Huancayo 2020 - De La Calle Castro , Anahi Indira (2021)
Objective: To determine the relationship between knowledge and practice of the use of personal protective equipment in the context of COVID 19 in the health personnel of the ICU service of the hospital el Carmen Huancayo 2020. The area of study corresponds to medical and health sciences. Material and methods: The method of this research will be scientific which consists of a research method mainly used. The research design is correlational, non-experimental and cross-sectional, the type of research, according to the purpose will be basic, the level of research will be descriptive - correlational. Results: The results show that 56% of the ICU personnel of Hospital El Carmen have an average knowledge of the use of PPE and 68% comply moderately with the use of PPE in the Covid - 19 context. Conclusion: We conclude that there is a significant relationship between the level of knowledge and the application of the measures of the ICU personnel of Hospital El Carmen,2020. (p value=0.001<0.05).